Describing the diwa ng lunan of San Juan City - Ozaeta, Emilio U. (Espasyo : Journal of Philippine Architecture and Allied Arts, 2012)
This article describes the phenomenological research undertaken to describe the architectural Spirit of Place of an urban locale with a unique rural demeanor. Using a methodology of informal interviews and photo documentation, data consisting of the community's impressions on its identity and the mirroring expressions of its designed environment were documented. The data was then subjected to a discursive analysis through a method developed by the author from earlier parallel research studies. A resultant detailed description embodied in the metaphor of Water was later affirmed by the community.